Une identité impériale sans Empire? Le sens de la politique de décolonisation britannique - Virginie Barrier-Roiron (Revue LISA)
Britain’s history as a nation and a great power cannot be dissociated from the concept of imperialism. The object of this article will be to study the way Britain managed to adapt her imperial identity to the post-colonial world that her own decolonisation policy contributed to pace. As the shaping of decolonisation in Africa accelerated at the end of the 1950s, the Commonwealth of Nations was considered by Britain as an ideal through which the Empire and its assets could survive. Because of the Rhodesian deadlock, the former colonial power was put in the dock by her African Commonwealth partners in 1966. This provoked an unprecedented crisis within the Commonwealth of Nations. Through a very symbolical process, the British Prime Minister managed to reverse the situation and declared Britain’s independence within the post-colonial association. After the Rhodesian crisis, Britain was no longer an imperialist power, but her imperial identity and ambitions on the world political scene survived through the Commonwealth of Nations and can also be identified today in Tony Blair’s vision of Britain as a “pivotal partner”, a link between North and South. Though the Commonwealth Rhodesian crisis, Britain managed to reconcile her imperial identity with her post-colonial responsibilities. If the Commonwealth is no longer considered as the main pillar of Britain’s international role in the world, it remains an important element through which an idea of Britain’s global role, which remains imperial in essence, is still promoted. In fact, in spite of the crisis of identity she underwent in the middle of the 1960s, we may say that, at the end of the day, Britain never renounced her imperial identity.